1994
DOI: 10.2135/cropsci1994.0011183x003400030020x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Response to NaCl Stress in Salt‐Tolerant and Salt‐Sensitive Cultivars of Cotton

Abstract: The mechanism(s) importing salt tolerance to plants remains unresolved. Although cotton (Gossypium hirsutum L.) is classified as salt‐tolerant plant, variation in salt tolerance has been observed among different cultivars. The purpose of this study was to determine if more salt‐tolerant cultivars contain higher constitutive or inducible levels of antioxidants than more salt‐sensitive cultivars. Greenhouse‐grown salt‐tolerant (cv. Acaia 1517‐88 and Acala 1517‐SR2) and salt‐sensitive (cv. Deltapine 50 and Stonev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
317
1
6

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 644 publications
(348 citation statements)
references
References 0 publications
24
317
1
6
Order By: Relevance
“…Feierabend et al (1992) have shown that under stress conditions inactivation of CAT is linked to H 2 O 2 accumulation. Loss of CAT activity due to salt stress in cotton (Gossett et al, 1994), sunflower (Santos et al, 2001), and rice (Lee et al, 2001), as well as due to photo-oxidative stress in tobacco chloroplasts (Miyagawa et al, 2000), is consistent with our results for J. curcas. The inhibition of CAT and APX activities by salt stress may be a consequence of downregulated gene expression or degradation, denaturation and/or inhibition/ inactivation of these proteins (Feierabend et al, 1992;Lee et al, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…Feierabend et al (1992) have shown that under stress conditions inactivation of CAT is linked to H 2 O 2 accumulation. Loss of CAT activity due to salt stress in cotton (Gossett et al, 1994), sunflower (Santos et al, 2001), and rice (Lee et al, 2001), as well as due to photo-oxidative stress in tobacco chloroplasts (Miyagawa et al, 2000), is consistent with our results for J. curcas. The inhibition of CAT and APX activities by salt stress may be a consequence of downregulated gene expression or degradation, denaturation and/or inhibition/ inactivation of these proteins (Feierabend et al, 1992;Lee et al, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…The ratios of AsA to DAsA and of GSH to GSSG decrease under oxidative stress (Law et al, 1983;Gossett et al, 1994). Although the ratios of both AsA/DAsA and GSH/GSSG were lower in Al-treated than in control leaves, AsA and GSH still accounted for more than 90 % of the total glutathione pool and ascorbate pool in the Al-treated leaves (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…The higher SOD activity in RH30 resulted in a greater level of H 2 O 2 , and therefore caused higher cellular damage in RH30 than Alankar. Gossett et al 45 reported that higher SOD activity without complementary increase in the ability to scavenge the formed H 2 O 2 can result in the increased cellular damage. Further, higher increase of CAT, APX and GR activity in Alankar resulted in efficient scavenging of Cd-induced ROS than RH30, where the activity of these enzymes was either less or reduced in comparison to the control.…”
Section: Resultsmentioning
confidence: 99%